INTRODUCTION OF A CLINICAL CASE OF PREECLAMPSIA/HYDROPS FETALIS SUCCESSFULLY TREATED AT THE MILITARY HOSPITAL 91 - Hoang Thi Kim Thai; Le Anh Tuyet; Dang Minh Duc; Do Quang Phu (Tạp chí Y học Quân sự, 2022)
Hydrops fetalis is a rare condition of obstetric emergency (accounted for 0.1% of births). This is an extremely serious obstetric complication because the risk of fetal death is very high. In case the fetus is still developing, the risk of birth defects caused by Hydrops fetalis is up to 85%, mainly on children with brain damage. Hydrops fetalis caused loss of function of the placenta, large amounts of fluid in the placental tissues, increase volume and weight. Military Hospital 91 has early diagnosed and successfully treated pregnant women with preeclampsia/Hydrops fetalis, anemia, fetal distress by active cesarean section. This was the optimal method for the mother's emergency, prevention of Retained placenta, bleeding, uterine atony, and postoperative infection.